Stres Akademik sebagai Pemicu Cyberloafing: Peran Status Mahasiswa Pekerja - Khinanta Azzahra Al Jannah; Andik Matulessy; Nindia Pratitis (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
Abstract The combination of studying and working places extra responsibilities on individuals, which can heighten stress within the educational setting. This situation may result in unproductive actions like engaging in online distractions during study time. This research intends to investigate how academic stress correlates with cyberloafing among students who also have jobs. A sample of 160 active students from the University of 17 Agustus 1945 in Surabaya was chosen using purposive sampling methods. The instruments utilized for this research comprise the Academic Stress Scale, grounded in Gadzella's theory, and the Cyberloafing Scale, derived from Akbulut's theory. Both measures have undergone tests for validity and reliability. The analysis through simple regression reveals a noteworthy positive correlation between academic stress and cyberloafing behavior. The results suggest that as academic stress rises, the likelihood of engaging in cyberloafing also increases. It is anticipated that these findings will be valuable for managing academic stress and provide useful insights for educators to help minimize ineffective online activities during learning sessions. Keywords: Academic stress; cyberloafing; dual role; working students. Abstrak Peran ganda sebagai mahasiswa dan pekerja menciptakan tuntutan tambahan yang dapat meningkatkan stres di lingkungan akademis. Kondisi ini bisa menimbulkan perilaku negatif seperti cyberloafing selama proses belajar. Penelitian ini bertujuan untuk mengeksplorasi hubungan antara stres akademik dan cyberloafing di kalangan mahasiswa yang juga bekerja. Sebanyak 160 mahasiswa aktif dari Universitas 17 Agustus 1945, Surabaya, dipilih dengan menggunakan metode purposive sampling. Alat yang digunakan dalam penelitian ini meliputi Skala Stres Akademik yang berdasarkan teori Gadzella dan Skala Cyberloafing yang diadaptasi dari teori Akbulut. Keduanya telah diuji untuk validitas dan reliabilitasnya. Menurut analisis regresi sederhana, ada korelasi positif yang signifikan antara stres akademik dan cyberloafing. Temuan ini menunjukkan bahwa tingkat stres akademik terkait dengan kemungkinan cyberloafing. Diharapkan hasil ini dapat memberikan kontribusi dalam pengelolaan stres akademik dan memberikan panduan praktis bagi para pendidik untuk mengurangi perilaku online yang tidak produktif selama kegiatan belajar. Kata kunci: Stres akademik; cyberloafing; peran ganda; mahasiswa yang bekerja.